The role of microtubules in the regulation of epithelial junctions. Issue 3 (3rd July 2018) - Vasileva, Ekaterina; Citi, Sandra
ABSTRACT: The cytoskeleton is crucially important for the assembly of cell-cell junctions and the homeostatic regulation of their functions. Junctional proteins act, in turn, as anchors for cytoskeletal filaments, and as regulators of cytoskeletal dynamics and signalling proteins. The cross-talk between junctions and the cytoskeleton is critical for the morphogenesis and physiology of epithelial and other tissues, but is not completely understood. Microtubules are implicated in the delivery of junctional proteins to cell-cell contact sites, in the differentiation and spatial organization of the cytoplasm, and in the stabilization of the barrier and adhesive functions of junctions. Here we focus on the relationships between microtubules and junctions of vertebrate epithelial cells. We highlight recent discoveries on the molecular underpinnings of microtubule-junction interactions, and report new data about the interaction of cingulin and paracingulin with microtubules. We also propose a possible new role of junctions as "molecular sinks" for microtubule-associated signalling proteins.